Assessing Service Quality using Data Envelopment analysis Case study at the Iraqi Middle East Investment Bank - حسن, شفاء بلاسم; عكاب, محمد مهدي (Journal of Economics and Administrative Sciences, 2017)
The use of data envelopment analysis method helps to improve the performance of organizations in order to exploit their resources efficiently in order to improve the service quality. represented study a problem in need of the Iraqi Middle East Investment Bank to assess the performance of bank branches, according to the service quality provided, Thus, the importance of the study is to contribute using a scientific and systematic method by applying  the data envelopment analysis method in assessing the service quality provided by the bank branches, The study focused on achieving the goal of determining the efficiency of the  services quality provided by the bank branches manner which reflect the extent of utilization of available resources, which were represented by (number of managers, number of employees, number of savings accounts, number of current accounts, number of credit accounts) to improve the service quality that have been measured according to the dimensions of (tangibility, reliability, responsiveness, Assurance, empathy). The study was applied in number of  branches in Baghdad city, which included branches (AL-Raaesie, tabark, alnoman, alzahir, altqdm, almstqbl, alnjah and alghoson), has confirmed the results of the study to achieve high efficiency of the  service quality for A number of bank branches, through the utilization of resources in an efficient, and therefore the study recommends using data envelopment analysis to assessing of service quality at All branches of the bank